When community reintegration is not the best option: interethnic violence and the trauma of parental loss in South Sudan. (26th August 2015) - Muller, Brigitte; Munslow, Barry; O'Dempsey, Tim
Summary: The magnitude of violence and human loss in conflict settings often exceeds the caring capacity of traditional support systems for orphans. The aim of this study is to understand the developmental context for children experiencing armed conflict, parental loss, extreme poverty, violence and social exclusion in a setting affected by interethnic violence. This article challenges the received wisdom that community reintegration is always better than institutional provision. Using a case study employing interviews, focus groups, workshops and observations, we examined how children's experiences of armed violence and parental loss affected their mental well‐being, and their relationships within their community. Emerging findings such as experienced violence and psychological distress were further investigated using a cross‐sectional survey design to explore the generalisability or transferability of theories or conclusions drawn from qualitative data. Findings showed that parental loss had a major impact on children's lives in the context of armed violence. Four main outcomes of orphanhood emerged: (i) facing the situation and evading harm (feelings of rejection and stigmatisation); (ii) trauma exposure and mental health effects (associations of orphanhood with adverse mental health outcomes and the number and type of experienced trauma); (iii) dealing with psychological distress (seeking caring connections and decreased feelings of isolation); and (iv) education and acceptance (increasing knowledge, skills and attitude and being respected in their community). We discuss the role that contexts such as armed violence, parental loss and social exclusion play for children's mental well‐being and their implications for psychosocial interventions and orphan care in humanitarian settings. Copyright © 2015 John Wiley & Sons, Ltd.